Canadian 24-h Movement Guidelines, Life Stress, and Self-Esteem Among Adolescents - Sampasa-Kanyinga, Hugues; Lien, Amanda; Hamilton, Hayley A.; Chaput, Jean-Philippe (Frontiers in Public Health, 2022)
Background: Adolescence is often considered a period of heightened stress, and healthy active living behaviours may help those experiencing it to better cope with life stressors and increase their self-esteem. The 24-hour movement guidelines for children and adolescents recommend ≥60 minutes per day of moderate-to-vigorous physical activity, ≤2 hours per day of recreational screen time, and 9-11 hours of sleep per night for school-aged children or 8-10 hours per night for adolescents. The objective of this study was to examine the association of meeting the 24-hour movement guidelines with life stress and self-esteem among students in Ontario, Canada. Methods: Self-reported data on movement behaviours, life stress and self-esteem were derived from the 2019 cycle of the Ontario Student Drug Use and Health Survey, a cross-sectional and province-wide survey of students in grades 7-12 aged 11 to 20 years (N=6,932). Multivariable ordered logistic regression analyses were adjusted for the complex sample design of the survey and for important covariates. Results: Overall, meeting all combinations of movement behaviour recommendations were associated with lower life stress and better self-esteem compared with meeting none of the recommendations, except meeting the physical activity only or screen time only recommendations that were not associated with lower life stress. Meeting all 3 recommendations was associated with lower life stress (OR: 0.40; 95 CI: 0.30–0.53) and better self-esteem (OR: 0.29; 95% CI: 0.21–0.40). There was a dose-response gradient between the number of recommendations met (3>2>1) and lower life stress (p<0.001) and higher self-esteem (p<0.001), with meeting all 3 recommendations being the best combination. Conclusions: These findings suggest that meeting the recommendations of the 24-hour movement guidelines is associated with lower life stress and better self-esteem among adolescents.